Do geossistema-território-paisagem à cartografia antropofágica das paisagens: proposta para compreensão da formação histórica e ocupação do solo litorânea do Recife-PE - Silva Filho, Luiz Carlos da (2021)
The coastal environment has been an object of study over the years due to its dynamic and sensibility to environmental variations, and because it has high ecological, social, economic, and cultural relevance. From the second half of the twentieth century, the spatial fragment legally constituted as the Coastal Zone has been reconfigured in its socio-environmental aspects and in its landscape. Considering these aspects, this work aims to comprehend the evolutive process of the last seven decades of use and occupation of the Coastal Landscape in the districts of Boa Viagem, Pina, and Brasília Teimosa, and develop an hodós-metá for Geography based on Anthropophagic Cartography of Landscapes, collaborating with the understanding of G-TP System. For this purpose, we adopted two methodological approaches. The first one is described as metá-hodós, as we conducted the acquisition stages of orthophoto mosaics granted by the City Hall of Recife, PE (1950, 1970, 1980, and 1990) and satellite images cataloged by the INPE and EarthExplore - USGS (2006-2017). We also classified Urban Landscapes Morphology Typologies, validated images with TerraView with the GeoDMA plug-in, and field data. The second stage is described as Hodós-Metá, and we made use of Geophotography to carry out the visual captures and the application that was proposed in this work, titled as Anthropophagic Cartography of Landscapes, with the purpose to understand the subjectivity of human beings in the field and their relationship with nature, in order to provide an understanding of the human-nature relationship. As a result, we identified that the evolution of the historical formation of both Boa Viagem and Pina districts took place in different ways, interconnected by the relation with the increase of the land value over the years. Boa Viagem is known as the place where the wealthiest people reside, which is valued by the subnormal condition of the “mocambos'' in flooded areas, found in the Pina district in the first decades of the twentieth century, which devalued it for many years, and made most improvements and investments go to the district of Boa Viagem. Brasília Teimosa district is formed from a landfill known at the time as Areial Novo, a piece of land that was intended for improvement works at the Port of Recife, recognized in the 1950s by President Juscelino Kubitschek and, therefore, called by its current name, and decades later it became a Special Social Interest Zone - ZEIS, by the Law 16176/1996. With the help of supervised classifications, we identified that the total area of the three districts, Boa Viagem, Pina, and Brasília Teimosa, corresponds to 1,520 ha, and between 1950-2010 the building area had an increase of 568% (780 ha of total area), the vegetated area reduced -56% (391.77 ha of the total area), the vegetated area with buildings reduced -55% (86.96 ha of the total area), the beach area reduced -67% (41.78 ha of the total area ), rivers and canals reduced -58% (180.59 ha of the total area), and the shrimp farming area had an increase of 153% (42.28 ha of the total area). From the hodós-metá developed, we carried out an ethnic cartographic experiment using the Anthropophagic Cartography of Landscapes in the Ilha de Deus, where we submerged into an affective field and a two-way street in the construction of trust bonds, from which we registered and captured the main movements of individuals in their territory. Therefore, we can understand how humans interact among the main elements of the landscape in a symbiosis process between these people and nature. Finally, we concluded that the analyzed districts underwent several processes of urban landscape reconfiguration, which modified the forms and structures that were present in the landscape. And with the use of Anthropophagic Cartography of Landscapes and Geophotography, we discovered, in a horizontal view, the relationships built by human beings with nature and place.